Subclinical Agoraphobia Symptoms and Regional Brain Volumes in Non-clinical Subjects: Between Compensation and Resilience? - Besteher, Bianca; Squarcina, Letizia; Spalthoff, Robert; Bellani, Marcella; Gaser, Christian; Nenadić, Igor; Brambilla, Paolo (Frontiers in Psychiatry, 2018)
Background: Symptoms of anxiety are present not only in panic disorder or other anxiety disorders, but are highly prevalent in the general population. Despite increasing biological research on anxiety disorders, there is little research on understanding subclinical or sub-threshold symptoms relating to anxiety in non-clinical community samples, which could give clues to factors relating to resilience or compensatory changes. Aims: This study focused on brain structural correlates of subclinical anxiety / agoraphobia symptoms from a multi-centre imaging study. Methods: We obtained high-resolution structural T1 MRI scans of 409 healthy young participants and used the CAT12 toolbox for voxel-based morphometry (VBM) analysis. Subjects provided self-ratings of anxiety using the SCL-90-R, from which we used the phobia subscale, covering anxiety symptoms related to those of panic and agoraphobia spectrum. Results: We found significant (p<0.05, FDR-corrected) correlations (mostly positive) of cortical volume with symptom severity, including the right lingual gyrus and calcarine sulcus, as well as left calcarine sulcus, superior, middle and inferior temporal gyri. Uncorrected exploratory analysis also revealed higher GMV in anterior cingulate cortex, orbitofrontal cortex and insula. Conclusions: Our findings show brain structural associations of subclinical symptoms of anxiety, which overlap with those seen in panic disorder or agoraphobia. This is consistent with a dimensional model of anxiety, which is reflected not only functionally but also on the structural level.